2015
DOI: 10.15740/has/rjahds/6.2/93-98
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding water washed neem (Azadirachta indica) seed cake and salt sprinkled neem (Azadirachta indica) leaves on blood parameters, feed conversion efficiency and economics of feeding in Osmanabadi kids

Abstract: Twenty four Osmanabadi weaned male kids with average live weight of 10.80 kg (5-6 months old) were divided into four equal groups in a Randomized Block Design and fed with water washed neem (Azadirachta indica) seed cake (WWNSC) and salt (2%) sprinkled neem (Azadirachta indica) leaves for 182 days to study the effect on blood parameters, feed conversion efficiency and economics of feeding. The kids (T 0) were fed with control diet without WWNSC and salt sprinkled neem leaves, (T 1) WWNSC (15% DCP) individually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…With comparable DM intake, weight gain as well as digestibility in all concentrate rations achieved with up to 50% substitution of concentrate in ration, less cost can be achieved with rapid growth rate of rabbits. Korake et al (2015) [6] reported in their experiment that feeding cost of live weight gain per kilogram in T 0 , T ).The results were in agreement with those of Radhakrishnan (2005a) [9] conducted experiment with weaned male kids fed with complete ration containing neem leaves at 0,20,40 and 60 percent level as roughage source and reported lower feeding cost per kilogram live weight gain in treatment group as compared to control. Radha Krishnan (2005) [9] showed the Madrared lamb fed with ration containing 60 percent of green fodder hay (T 1 ) and ration contained 60 percent of Neem: SS: GNH25:37.5:37.5, (T 3 ) Subabul: GNH:RS25:37.5:37.5 and (T 4 ) Gliricidia: GNH:RS 25:37.5:37.5 and recorded lower feeding cost per kilogram live weight gain in treatment groups as compare to control.…”
Section: Economics Of Feedingsupporting
confidence: 74%
“…With comparable DM intake, weight gain as well as digestibility in all concentrate rations achieved with up to 50% substitution of concentrate in ration, less cost can be achieved with rapid growth rate of rabbits. Korake et al (2015) [6] reported in their experiment that feeding cost of live weight gain per kilogram in T 0 , T ).The results were in agreement with those of Radhakrishnan (2005a) [9] conducted experiment with weaned male kids fed with complete ration containing neem leaves at 0,20,40 and 60 percent level as roughage source and reported lower feeding cost per kilogram live weight gain in treatment group as compared to control. Radha Krishnan (2005) [9] showed the Madrared lamb fed with ration containing 60 percent of green fodder hay (T 1 ) and ration contained 60 percent of Neem: SS: GNH25:37.5:37.5, (T 3 ) Subabul: GNH:RS25:37.5:37.5 and (T 4 ) Gliricidia: GNH:RS 25:37.5:37.5 and recorded lower feeding cost per kilogram live weight gain in treatment groups as compare to control.…”
Section: Economics Of Feedingsupporting
confidence: 74%